English Students’ and Lecturers’ Difficulties in Teaching and Learning of Participle Phrases - Haryanti, Sri; Haryono, Purwo; Yuwono, Suhud Eko (International Journal of Active Learning, 2022)
This research aimed at identifying and describing students’ and lecturers’ difficulties in teaching and learning of participle phrases and achieving the same perception of their difficulties in teaching and learning of participle phrases. The sources of the data are the English students and lecturers of English Education Study Program, University of Widya Dharma Klaten in 2021. Analyzing data by descriptive qualitative method, this research found out that students have difficulty in differentiating –ing form verb as predicate, modifier, and gerund; past participle verb especially irregular verb as predicate and as modifier; irregular past participle verbs as predicate of a sentence in perfect tenses and passive voice from those which are as participle phrases. Meanwhile, lecturers’ difficulties are that participle phrases have many patterns. They are patterns in active activity, passive activity, present form, perfect form, etc.; the theories of participle phrases that consist of some different concepts. Therefore, the students and lecturers have the same perception that the patterns of participle phrases which are different in active and passive meaning, especially in irregular verb formation need to be got more attention; the theories of participle phrase which are complicated need to be made simple and comprehensible.